Investor sentiment and speculative bond yield spreads - Gozde Turkmen Muldur; Serkan Yılmaz Kandir; Yıldırım Beyazıt Onal (Foundations of Management, 2019)
The valuation of risky debt is central to theoretical and empirical work in corporate finance. Although much is known on the returns and valuation of bonds, there is hardly a consensus on the risk components of the yield spreads. This article aims to investigate the effect of investor sentiment as a systematic risk factor on speculative bond yield spreads. After applying correlation analysis to determine the strength of linear association between these two variables, a vector autoregressive (VAR) analysis and impulse response tests are used to examine the relationship between these two variables. The sample period extends from January 1997 to August 2014. In the VAR models, speculative bond spreads and consumer confidence index are used as endogenous variables. The results show that sentiment covaries with the yield spread and have a negative effect on them. The spread level of the previous period seems to be a statistically significant determinant of the current period sentiment. Empirical findings imply that investor sentiment is a systematic risk factor in risky bond markets.
Keywords: G112; G15; G40; 650; investor sentiment; speculative bonds; bond spreads; VAR analysis; junk bonds